Ujawnianie i prezentacja informacji sprawozdawczej - Hasik, Wojciech; Kwiecień, Mirosława (Presentation and Disclosure of Financial Information, 2007)
In this paper the authors indicate the identity of terms: accounting policy and balance sheet policy. They justify the necessity of presenting them in the financial statement as resulting from legal provisions of the Act on Accounting.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 53-59